Preoperative antibiotic prophylaxis in a single tertiary hospital in Slovenia—the role of education in recommendation compliance: Predpisovanje perioperativne antibiotične zaščite v terciarni bolnišnici v Sloveniji - vloga edukacije pri izboljšanju predpisovanja - Žnidarič, Matej; Vogrin, Matjaž; Moličnik, Andrej; Mujezinović, Faris; Kavčič, Niko; Gorišek Miksić, Nina (Acta Medico-Biotechnica, 2022)
Purpose: The aim of the present study was to evaluate the impact of an educational intervention package on perioperative antimicrobial prophylaxis (PAP) prescription practice in three elective procedures—total hip arthroplasty (THA), caesarean section (CS), and radical prostatectomy (RP)—in a single tertiary care hospital in Slovenia.Methods: An interventional study was performed to evaluate the impact of an educational intervention package on PAP compliance. PAP prescription practices for three elective types of surgery (THA, CS, and RP) were observed. Thirty operative reports for each type of surgical procedure were evaluated according to indication, timing of preoperative prophylaxis administration, antibiotic selection and dosage, and total prophylaxis duration. This was followed by an educational intervention package that included a discussion with department leaders led by an infectious disease specialist and an educational seminar and discussion for surgeons, supplemented by PAP recommendations provided as pocket reminders. Then, the compliance with PAP recommendations for the same types of procedures performed in the post-interventional period (3–6 months after the intervention) was evaluated again.Results: Complete pre-interventional compliance with local guidelines was observed in 67%, 70%, and 3.3% of THA, CS, and RP cases, respectively. A major deviation from PAP recommendations was observed in the timing of preoperative PAP administration before surgery and in the total PAP duration A deviation from recommendations for RP, which is a major surgical procedure, was observed as a longer postoperative PAP duration compared to the intraoperative course. In the post-interventional period, an improvement in total compliance with PAP recommendations was observed in 80.0%, 90.0%, and 50.0% of THR, CS, and RP procedures, respectively.Conclusion: Our study revealed an improvement in adherence to PAP recommendations after an educational intervention package for selected procedures at the University Medical Centre Maribor. This simple intervention can have an important impact on patient care quality by reducing antimicrobial medication use, resistance development, and treatment cost.
Keywords: perioperative antibiotic prophylaxis, recommendations, compliance, surgery, educational intervention